Aplikasi Edible Coating Berbasis Polisakarida untuk Mengurangi Kerusakan Pascapanen - Rahmawati, Ani; Afina, Afina (CV. Green Publisher Indonesia, 2025)
Post-harvest damage to horticultural commodities is one of the main causes of a decline in product quality and quantity of up to 30–40%. Efforts to reduce this damage can be done through the application of polysaccharide-based edible coatings that are able to form a thin layer as an inhibitor of respiration rate, water loss, and microbial growth. This study aims to analyze the effectiveness of polysaccharide-based edible coatings on the quality and extent of damage to horticultural products during storage. The experimental method was applied using three types of polysaccharides—pectin, chitosan, and carboxymethyl cellulose (CMC)—with testing for the rate of weight loss, hardness, color, and total microbial colonies. The results showed that the edible coating treatment significantly reduced damage by up to 45% compared to controls. Chitosan shows the highest effectiveness especially in suppressing microbial growth, while pectin is effective in maintaining texture. These findings reinforce that polysaccharide-based edible coatings can be used as an environmentally friendly, safe, economical, and potential post-harvest technology for commercial applications.